Reading Craig Keener On Spirit Hermeneutics: Reading Scripture in Light of Pentecost - Oliverio, L. William; Keener, Craig S. 1960- (2017)
In this essay, I contend that Craig Keener’s Spirit Hermeneutics is a major contribution to charismatic-pentecostal biblical hermeneutics and is likely to become a classical text on the subject. Keener develops an ecumenical rather than sectarian pentecostal hermeneutic that addresses both the contextuality of the original texts and that of contemporary interpreters, valuing multiple legitimate interpretations while also holding to the author and Spirit’s design of the text as grounding interpretive meaning. Further, Keener’s hermeneutic provides the biblical hermeneutic for an emerging pentecostal theological paradigm that can be developed through further attention to the relationship between Keener’s biblical hermeneutics and theological hermeneutics, cultural hermeneutics, present horizons of interpretation, and the religious and fleshly forces arrayed against the Spirit hermeneutics for which he advocates.
Keywords: Spirit Hermeneutics -- biblical hermeneutics -- theological hermeneutics -- cultural hermeneutics -- Craig S. Keener -- paradigms -- authors; Rezension